Fertilizer trade under market liberalizations: Preliminary evidence from Kenya - Omamo, Steven Were; Mose, L.O. (Elsevier, 2001)
This paper reports results of a study aimed at identifying broad demand-side and supply-side influences on trade in inorganic fertilizers in Kenya, where, following decades of government control, the fertilizer market has been fully liberalized. Multiple regression analysis using data from a country-wide survey of fertilizer traders indicates that significant demand-side factors include agroecological conditions and maize market prices in the regions in which fertilizer traders operate. On the supply side, the number of years in fertilizer trading and access to credit are important. Implications for policy and research are drawn.